Managing Acute Insomnia in Prison: Evaluation of a "One-Shot" Cognitive Behavioral Therapy for Insomnia (CBT-I) Intervention. Issue 6 (2nd November 2019) - Randall, Charlotte; Nowakowski, Sara; Ellis, Jason G.
ABSTRACT: Objectives/Background: Insomnia is a serious condition that affects over 60% of the prison population and has been associated with aggression, anger, impulsivity, suicidality, and increased prison health care use. Nonpharmacological interventions for prison inmates are scarce despite the high prevalence and significant consequences of insomnia among those incarcerated. The aim of the present study was to examine the preliminary efficacy and effectiveness of a one-shot session of cognitive behavioral therapy for insomnia (CBT-I) for prison inmates with acute insomnia in an open trial. Method/Participants: The intervention consisted of one 60–70 min session of CBT-I and a self-management pamphlet. A consecutive series of 30 adult male offenders with acute insomnia from a UK prison completed measures of prospective sleep (daily sleep diary), insomnia symptoms severity (Insomnia Severity Index), and mood symptoms (Patient Health Questionnaire and General Anxiety Disorder) one week before and four weeks after receiving the intervention. Results: Pairwise t -tests revealed that a single shot of CBT-I was effective in reducing the severity of insomnia in adult male offenders ( t = [29], 12.65, p < 0.001). Further, the results demonstrated moderate to large effect sizes for reductions in depressive (dRM = 0.77) and anxious (dRM = 0.83) symptoms, as well as insomnia severity (dRM = 2.35). Conclusions: A single-shot session of CBT-I is effective in managing acute insomnia and mood (depression, anxiety) symptoms in adult male prison inmates. Future research should focus on testing if the single-shot CBT-I intervention can be implemented and disseminated in other settings and populations (e.g., female and juvenile or youth offenders).